"A Navegação que ensejou a vivência da docência: O percurso de construção da identidade e modo de atuação profissional" - André Leite Soares (2021)
navigation that led to the experience of teaching: the path of an identity construction and professional performance mode was built in the innocence of "white", empty, un-carved sheets, depicting the entry into teaching of an aspiring teacher (the author) and his experience. The cooperating school located in Vila Nova de Gaia was the context of the whole navigation experience, which allowed for a long journey in two secondary school classes (10th and 11th grades) and a primary school class (6th grade) from another cooperating school. The 11th grade class was guided in the teaching-learning process in an autonomous way, while the others in a shared way. The metaphor of navigation served as a structure for the whole process, mirroring the transition from the "ideal" to the real, where I tried to commit myself in an unknown context. The numerous learnings around the act of planning and implementation, and the importance of content knowledge and pedagogical content knowledge, led me to value the construction of my professional self. The bridges of connection created with the students and the turbulences and challenges at the level of teaching models and strategies, highlighting the area of physical fitness extension, were structural points in the process. If I did not go through them, I would be 'stuck' in old worries and fears. Furthermore, the impact of distance teaching, which although challenging, has been consistently navigated, along with the (re)construction of the issues around assessment and grading, were instrumental in the feeling of duty done, representing success in yet another navigation. The presence in the several meetings, the monitoring of the work of a class director, perceiving his demands, despite the not without participation, and the "look" over the several activities, allowed the understanding of the determinant role of all moments. The research study, sought to analyse the development of physical fitness in the context of Physical Education in high school students, in curricular physical education, throughout the school year. The results showed that the application of the training program had a positive effect in all the applied tests, apart from the HandGrip Strength Test. The analysis made by gender, age and body mass index did not show a clear interference of the variables in the effects of the program.